Glomus tumors of the nail bed: topographic anatomy and an algorithmic approach based on the topography - Civan, Osman; Güntürk, Özgün Barış; Özaksar, Kemal; Cavit, Ali; Özcanli, Haluk (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Purpose Glomus tumors are rare vascular pathologies characterized by a triad of symptoms: tenderness, pain and cold intolerance. In the hand they are highly concentrated under the nail bed. In this retrospective study, we aimed to present a topographic map of the location of glomus tumors in the nail bed and a map-based surgical approach algorithm to the subungual glomus tumors.Methods We prepared a nail bed map with 6 zones and named these zones as ulnar distal, ulnar proximal, central distal, central proximal, radial distal and radial proximal. With respect to the tumor location and the used surgical approach we retrospectively evaluated the intraoperative photos and the hospital records of patients who were operated between 2008–2019 and had the pathological diagnosis of glomus tumor. The examination records of the postoperative first year were evaluated for each patient retrospectively. A descriptive statistical analysis was performed. In addition we analyzed the described surgical approaches to excise a glomus tumor in the nail bed. The described approaches and the approaches used by us were matched with the localisation of the tumors in this study developing an algorithm for the surgical approach depending on the localisation of the nail bed glomus tumor.Results Finally 44 patients had inclusion criteria. The distribution of the glomus tumor was as follows: 2 were on ulnar distal (4.5 %), 9 on ulnar proximal (20.5 %), 1 on central distal (2.3 %), 18 on central proximal (40.9 %), 4 on radial distal (9.1 %) and 10 were on the radial proximal zones (22.7 %). 4 lateral approaches, 1 nail sparing and 39 transungual approaches were performed. We had one recurrence in a male patient operated by transungual approach.Conclusion Glomus tumors are mostly located on the central proximal part of the nail bed. Our glomus map and the algorithm we described might be helpful for the selection of the surgical approach for the glomus tumor.
Keywords: Glomus tumors; nail bed; surgical approach